A randomised controlled trial studying the effects of the copper intrauterine device and the injectable progestogen contraceptive on depression and sexual functioning of women in the Eastern Cape - Singata-Madliki, Mandisa (Division of Nursing and Midwifery, 2016)
A lack of contraception use and contraceptive method discontinuation are common causes of unintended pregnancy in the Eastern Cape. The most common reason for method discontinuation among childbearing women is the unacceptable side effects of their contraceptive choices. Both depression and sexual dysfunction are given as side effects of contraceptive use; however, there is little evidence to support these effects. This randomised, single-blind controlled trial conducted in East London, South Africa, Investigated the effects of the initiation of a long-acting injectable contraceptive, Depot Medroxyprogesterone Acetate (DMP A), compared with the initiation of a copper Intrauterine Contraceptive Device (Cu-IUD) after childbirth on depression and sexual functioning. After counselling, 242consenting pregnant women were randomised to receive DMP A or a Cu IUD within 48 hours of childbirth, in a ratio of 1:1. Primary outcome measures were depression and sexual dysfunction evaluated by validated instruments. Questionnaires were administered at baseline, and telephonically at one month and three months after randomisation. The telephonic interviewer was blinded to the participants' group allocation. English and Xhosa versions of the Beck Depression Inventory and the Edinburgh Postnatal Depression Scale were used to assess depression. The Arizona Sexual Functioning Scale was used to assess sexual functioning. For these primary outcomes, median scores between the intervention groups were compared, as well as the number of events (dichotomous data) in each intervention group. There relative effects of these interventions were summarised by calculating risk ratios, with 95% confidence intervals. Statistical tests used included the Shapiro-Wilk test, T-test, and Wilcoxon test. There were not consistently statistically significant differences in the risk of depression or sexual dysfunction between the intervention groups in this study. However, there was a trend towards more depression in the DMPA group which was statistically significant for mean EPDS score at the one month and for the BDI score three month assessments compared with the IUD group. There was also a trend to more sexual dysfunction with DMPA, but the only statistically significant difference was that fewer women in the DMPA group resumed sexual intercourse within the first month of treatment than in the IUD group. The author's recommendations from the study are that, firstly, family planning providers should inform women during contraceptive counselling that there is no certainty that DMPA causes depression and/or sexual dysfunction; however, it may do so in the postpartum period. Secondly, contraceptive users can continue to use DMPA with confidence as a convenient and effective method of preventing unintended pregnancy. Thirdly, the trend towards postpartum depression and sexual dysfunction in the DMPA group of this study justifies further research with a larger sample size, to include women from various social settings, and for a longer period of follow-up. Lastly, the Cu-IUD is a good alternative to DMPA in women who experience intolerable effects with the latter.